School Information Three Dimensional Animation Using Blender Version 2.79: School Information Three Dimensional Animation Using Blender Version 2.79 - Agam Beny Styawan; Nurhayati Nurhayati; Sari Ningsih (Jurnal Mantik, 2020)
With the development of the movie and gaming industry the which is currently a field of motion capture has experienced rapid growth Also supports the development of the film and gaming industry. Captured motion in animation, it is important to create characters that move realistically, in a situation that is not practical or too dangerous for an actor. To Obtain the natural motion with the motion capture technique is still very low, due to the availability of equipment and application of human motion capture technology in the world of animation is still very expensive in terms of both hardware and software used. One type of human motion capture system that Utilizes optical motion capture cameras. The purpose of this study is to Obtain a realistic movement and shorten the time penganimasian for 3D animation filmmaking.